The story of the hashtag(#): A practical theological tracing of the hashtag(#) symbol on Twitter - Van den Berg, J. A. (HTS teologiese studies, 2014)
The phenomenon relating to the popularity and impact of social media as an important expression of the new digital world, is already widely known and well-documented. In this research, the main focus will fall on a specific manner of expression associated with social media and, in particular, with the Twitter platform, namely the hashtag (#) symbol. This symbol has come to comprise an important expression in popular culture, and is generally associated with various dimensions of activities in the social media environment. Through the use of several examples from the recent past, the development and meaning of the hashtag will be explored and described. As part of this description, a motivation will be put forward as to why it is important, for the purposes of a practical theological involvement as expressed in the dimensions of a lived spirituality, to take cognisance of the hashtag and the world that is associated with it. Arising from this motivation, and in congruence with the strategic character of practical theology, perspectives will be mapped out with a view to the further use and meaning of a dynamic reading of the hashtag.